2003
DOI: 10.1002/ana.10528
|View full text |Cite
|
Sign up to set email alerts
|

Continuous growth of mean tumor diameter in a subset of grade II gliomas

Abstract: Serial magnetic resonance images of 27 patients with untreated World Health Organization grade II oligodendrogliomas or mixed gliomas were reviewed retrospectively to study the kinetics of tumor growth before anaplastic transformation. Analysis of the mean tumor diameters over time showed constant growth. Linear regression, using a mixed model, found an average slope of 4.1mm per year (95% confidence interval, 3.8-4.4mm/year). Untreated low-grade oligodendrogliomas or mixed gliomas grow continuously during the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
275
0
6

Year Published

2004
2004
2017
2017

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 442 publications
(301 citation statements)
references
References 11 publications
20
275
0
6
Order By: Relevance
“…The total mean diffusion was estimated based on two facts. First, Mandonnet et al (23), in a study of patients suffering from low-grade gliomas, reported that the diameter of the detectable part of the tumor expands about 4 mm per year. Second, one can show that the detectable diameter d obeys the asymptotic law (15) d͑t͒ ϳ 4 ͱD t, [12] for large time t, where D is the mean cell diffusion and the net proliferation constant for an exponential proliferation law.…”
Section: Choice Of Parametersmentioning
confidence: 99%
“…The total mean diffusion was estimated based on two facts. First, Mandonnet et al (23), in a study of patients suffering from low-grade gliomas, reported that the diameter of the detectable part of the tumor expands about 4 mm per year. Second, one can show that the detectable diameter d obeys the asymptotic law (15) d͑t͒ ϳ 4 ͱD t, [12] for large time t, where D is the mean cell diffusion and the net proliferation constant for an exponential proliferation law.…”
Section: Choice Of Parametersmentioning
confidence: 99%
“…Measurements of the radial growth rates of grade II astrocytomas AAs in patients who have not received adjuvant therapy demonstrate a modest annual increase of 2 mm/year. 4,5 Slow, persistent expansion characterizes these grade II-III astrocytomas.…”
Section: Accelerated Growth In Gbmmentioning
confidence: 99%
“…A mean tumor diameter increase of 4.1mm per year was reported in oligodendrogliomas or mixed gliomas on serial MR [17]. TMZ chemotherapy reversed this increase and led to an average tumor diameter decrease of 9.1 mm per year in one series [18].…”
Section: Discussionmentioning
confidence: 89%